A study on the effectiveness of zikir therapy on anxiety among nursing students during practical sessio / Abdul Muhaimin Abdul Aziz, Nur Atikah Md Aris, Wan Nor Sakinah Bwan Nor Azli Jasmi - Abdul Aziz, Abdul Muhaimin; Md Aris, Nur Atikah; Wan Nor Azli Jasmi, Wan Nor Sakinah (2015)
Introduction: Anxiety is one of the major factors among nursing students. The purpose of this study was to examine the effectiveness of zikir therapy in reducing anxiety among nursing students. Method: A Quasi experimental design was conducted. Fortyseven students were divided into intervention and control group through convenient sampling. The students in the intervention group were given five days zikir intervention during clinical session. While, the student in control group not received any intervention. Result: Anxiety level score among students showed there is significant different between intervention and control group by using non parametric test (Mann Whitney test). The finding detected that zikir intervention reduce anxiety level (p= 0.027 to 0.003). While using non parametric test (Wilcoxon Signed test) there is no significant different for pre and post test score in control group (p= 0.41). However, in intervention group there is significant different in pre and post test score (p<0.05). Conclusion: Therefore, the result indicated that zikir therapy decreased in level of anxiety after the intervention compared to control group. Thus, the result suggested that zikir therapy is effective at anxiety reduction.